Impact of ICT uses in food supply chain: a case study of Narsingdi vegetable supply chain - Huque, Md. Enamul (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.